Studi Deskriptif Peran Guru Sebagai Fasilitator Pada Pembelajaran IPS Di Kelas V SDN 12 Kota Bengkulu - Yani, Novi; Dadi, Sri; Yusuf, Syahril (Jurnal PGSD, 2018)
The  purpose  of  this  study  is  to describe  the  role  of  the  teacher  as  a  facilitator  in learning IPS class V SDN 12 Kota Bengkulu. The type of study used in this was descriptive      qualitative. The subjects of the research were the teacher and students of grade V SDN 12 Kota Bengkulu. The instrument of this study was the researcher by using the observation guidelines and interview guidelines. Technique of collecting data using observation and interview. The data obtained were analyzed by data reduction, data display and conclusion. Credibility test data through increasing persistence and triangulation. The results showed that as a facilitator in the learning IPS, the teacher already (1) Involving the students as the subject of learning, (2) Mastering of science to be studied, (3) Interesting and maintaining students interest. Based on the results of the study concluded that the role of teachers as facilitators of learning IPS has been implemented, but in the use of learning method and the use of instructional media must be improved again so that learning activities can be implemented more optimally.